ESTIMATION OF GUGGULSTERONE-Z IN GOKSHURADI GUGGULU USING REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - Gamit, Kanan G; Vyas, Niraj Y; Patel, Nishit D; Raval, Manan A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A study was aimed to estimate guggulsterone-Z (GZ) in Gokshuradi Guggulu (GG). Methods: An analytical method was developed and validated using Waters Alliance high-performance liquid chromatography system (Empower software), equipped with photodiode array detector. Separation was achieved using Phenomenex, C-18 (250 mmÃ—4.6 mm, 5 Î¼) column. Mobile phase consisted of acetonitrile:water (70:30,v/v). Flow rate was set to 1 ml/min and detection was performed at 251 nm. Results and Discussion: Validation parameters such as linearity, precision, accuracy, limit of detection, limit of quantification, and robustness were performed. Amount of GZ was estimated using linearity equation. Conclusion: GG was found to contain 0.815Â±0.03 g% w/w GZ. Validated method may be used as one of the parameters to standardize the formulation.